Strategies for Mitigating Microservice Anti-Patterns in the Pre-Migration of Monolithic Legacy Systems - Villaca, Guilherme L. D.; Silva, Ivonei F. da; Assunção, Wesley K. G.; Rocha, Rodrigo B.; Fermino, Gabriel C. (Anais da Escola Regional de Engenharia de Software (ERES); 2024: Anais da VIII Escola Regional de Engenharia de SoftwareDO - 10.5753/eres.2024.4273, 2024)
This article analyzes strategies for mitigating antipatterns during the pre-migration phase of monolithic systems to microservices architectures. Using a multi-method research approach, the study examines the challenges and best practices involved in this transition. The research highlights that Domain-Driven Design (DDD) and the Strangler Fig Pattern are essential strategies for the gradual decomposition and migration of systems. Key success factors also include modularization, effective management of coupling, and the implementation of automated testing. The analysis emphasizes the importance of considering the specific context when selecting migration strategies. Overall, the study identified 25 strategies and concluded that these approaches, when applied in the pre-migration phase, can effectively mitigate antipatterns during the transition to microservices.